DESKRIPSI KUALITAS AIR SUNGAI BATANG LAMPASI KOTA PAYAKUMBUH DI MUSIM HUJAN DAN MUSIM PANAS MELALUI ANALISA BOD, COD DAN TSS - Rahayu, Lisa (RC-INSTITUT, 2019)
Human activities from agricultural,industrial, household activities and the amount of the settlements result in domestic waste generated is increasing every year. The study aims to know and the contribution government and societies in Payakumbuh for maintaining the water pollution on Batang Lampasi river to measure thewater quality of the river bykey parameters water pollution. Water quality analisis conducted by examining and compare result analysis water quality the parameter when rainy season and summer,the parameter used are BOD, COD and TSS. Sampling was conducted at ten points, from upstream to downstream. The decline in river water quality is characterized by changes in the physical, chemical, biological and aesthetic quality of the river. The result showed domestic waste resulting significant increase in the result of the BOD, COD dan TSS parameters analysis in the summer compare to during the rainy season. Where as the parameter COD in the summer  each 45.8, 35.2, 39.1, 40.9, 49.5, 39.3, 45.5, 47, 36, 48.4 and for the value of COD in the rainy season each 3.22, 5.91, 7.51, 4.35, 10.2, 6.53, 6.53, 15.6, 9.53, 10.8 The value of river water quality standards based on PP number 82/2001 for the category second class river with COD parameter is 25 mg/L, BOD is 3 mg/L and TSS is 50 mg/L.